Ckobicby HMS Company / Laurian John Johnny... [et al.] - John Johnny, Laurian; Molek, Filletus; Mohammad, Saidah; Mansur, Muhd. Nazrin (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2014)
Ckobicby HMB company is a new company in Suria Sabah, Kota Kinabalu area. The company provide range of biscuit product in Kota Kinabalu. It is the goal of the company management to acquire local market share in the bookstore industry through a strong selection of products and services that gives great taste and quality to our customer.